A Selective Phosphodiesterase 10A Inhibitor Reduces L‐Dopa‐Induced Dyskinesias in Parkinsonian Monkeys. Issue 5 (6th March 2018) - Beck, Goichi; Maehara, Shunsuke; Chang, Phat Ly; Papa, Stella M.
ABSTRACT: Background: Phosphodiesterase 10A is a member of the phosphodiesterase family whose brain expression is restricted to the striatum. Phosphodiesterase 10A regulates cyclic adenosine monophosphate and cyclic guanosine monophosphate, which mediate responses to dopamine receptor activation, and the levels of these cyclic nucleotides are decreased in experimental models ofl ‐dopa‐induced dyskinesia. The elevation of cyclic adenosine monophosphate/cyclic guanosine monophosphate levels by phosphodiesterase 10A inhibition may thus be targeted to reducel ‐dopa‐induced dyskinesia. Objectives: The present study was aimed at determining the potential antidyskinetic effects of phosphodiesterase 10A inhibitors in a primate model of Parkinson's disease (PD). The experiments performed in this model were also intended to provide translational data for the design of future clinical trials. Methods: Five MPTP‐treated macaques with advanced parkinsonism and reproduciblel ‐dopa‐induced dyskinesia were used. MR1916, a selective phosphodiesterase 10A inhibitor, at doses 0.0015 to 0.05 mg/kg, subcutaneously, or its vehicle (control test) was coadministered withl ‐dopa methyl ester acutely (predetermined optimal and suboptimal subcutaneous doses) and orall ‐dopa chronically as daily treatment for 5 weeks. Standardized scales were used to assess motor disability andl ‐dopa‐induced dyskinesia by blinded examiners. Pharmacokinetics was also examined. Results: MR1916 consistently reducedl ‐dopa‐induced dyskinesia in acute tests ofl ‐dopa optimal and suboptimal doses. Significant effects were present with every MR1916 dose tested, but the most effective was 0.015 mg/kg. None of the MR1916 doses tested affected the antiparkinsonian action ofl ‐dopa at the optimal dose. The anti‐l ‐dopa‐induced dyskinesia effect of MR1916 (0.015 mg/kg, subcutaneously) was sustained with chronic administration, indicating that tolerance did not develop over the 5‐week treatment. No adverse effects were observed after MR1916 administration acutely or chronically. Conclusions: Results show that regulation of striatal cyclic nucleotides by phosphodiesterase 10A inhibition could be a useful therapeutic approach forl ‐dopa‐induced dyskinesia, and therefore data support further studies of selective phosphodiesterase 10A inhibitors for PD therapy. © 2018 International Parkinson and Movement Disorder Society